Cerebrospinal fluid concentrations of fluoroquinolones and carbapenems in tuberculosis meningitis - Maranchick, Nicole F.; Alshaer, Mohammad H.; Smith, Alison G. C.; Avaliani, Teona; Gujabidze, Mariam; Bakuradze, Tinatin; Sabanadze, Shorena; Avaliani, Zaza; Kipiani, Maia; Peloquin, Charles A.; Kempker, Russell R. (Frontiers in Pharmacology, 2022)
Background: Tuberculosis meningitis (TBM) is the most lethal form of TB. It is difficult to treat in part due to poor or uncertain drug penetration into the central nervous system (CNS). To help fill this knowledge gap, we evaluated the cerebrospinal fluid (CSF) concentrations of fluoroquinolones and carbapenems in patients being treated for TBM. Methods: Serial serum and CSF samples were collected from hospitalized patients being treated for TBM. CSF was collected from routine lumbar punctures between alternating timepoints of 2 and 6 hours after drug administration to capture early and late CSF penetration. Rich serum sampling was collected after drug administration on day 28 for non-compartmental analysis. Results: Among 22 patients treated for TBM (8 with confirmed disease), there was high use of fluoroquinolones (levofloxacin, 21; moxifloxacin, 10; ofloxacin, 6) and carbapenems (imipenem, 11; meropenem, 6). Median CSF total concentrations of levofloxacin at 2 and 6 hours were 1.34mg/L and 3.36 mg/L with adjusted CSF/serum ratios of 0.41 and 0.63, respectively. For moxifloxacin, the median CSF total concentrations at 2 and 6 hours were 0.78mg/L and 1.02mg/L with adjusted CSF/serum ratios of 0.44 and 0.62. Serum and CSF concentrations of moxifloxacin were not affected by rifampin use. Among the 76 CSF samples measured for carbapenem concentrations, 79% were undetectable or below the limit of detection. Conclusions: Fluoroquinolones demonstrated high CSF penetration indicating their potential usefulness for the treatment of TBM. In contrast, carbapenems had lower than expected CSF concentrations, casting doubt on their utility.